High Latitude Changes in Ice Dynamics and Their Impact on Polar Marine Ecosystems - Moline, Mark A.; Karnovsky, Nina J.; Brown, Zachary; Divoky, George J.; Frazer, Thomas K.; Jacoby, Charles A.; Torres, Joseph J.; Fraser, William R. (Annals of the New York Academy of Sciences, 2008)
Polar regions have experienced significant warming in recent decades. Warming has been most pronounced across the Arctic Ocean Basin and along the Antarctic Peninsula, with significant decreases in the extent and seasonal duration of sea ice. Rapid retreat of glaciers and disintegration of ice sheets have also been documented. The rate of warming is increasing and is predicted to continue well into the current century, with continued impacts on ice dynamics. Climate-mediated changes in ice dynamics are a concern as ice serves as primary habitat for marine organisms central to the food webs of these regions. Changes in the timing and extent of sea ice impose temporal asynchronies and spatial separations between energy requirements and food availability for many higher trophic levels. These mismatches lead to decreased reproductive success, lower abundances, and changes in distribution. In addition to these direct impacts of ice loss, climate-induced changes also facilitate indirect effects through changes in hydrography, which include introduction of species from lower latitudes and altered assemblages of primary producers. Here, we review recent changes and trends in ice dynamics and the responses of marine ecosystems. Specifically, we provide examples of ice-dependent organisms and associated species from the Arctic and Antarctic to illustrate the impacts of the temporal and spatial changes in ice dynamics.